Analisis kelembagaan pemasaran dan margin tataniaga hasil perikanan tangkap didesa buluh cina kecamatan siak hulu kabupaten kampar provinsi riau - Ramizan, Dani; Yulinda, Eni; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on 29 January to 5 February 2013 in the Buluh Cina Village Siak Hulu district Kampar Riau Province. This study used survey method with determined sample purposively was 20 respondents. The purposed of this study was determined marketing instutions and marketing margin in research location.Marketing Institutional of fishermen consist of fishermen, distribution consist of fishermen, distributors, and dealers outside the district who come directly to the villageof Buluh Cina. Average price sale every type of fish in each marketing board when viewed from a raised catch, fishermen sold fish catch in Rp.43.000,-/Kg, middle level bought fish with average price in Rp. 49.000,-/Kg, and floor trader average purchase price in Rp. 52.000, -/Kg.Keyword :Analysis ,Marketing Margin,Marketing